Program specifications for bachelor in engineering (petroleum) - Ismail, Issham (Faculty of Chemical & Natural Resources Engineering, 2008)
The UTM Petroleum Engineering Program Specifications (for the period of 2005-2008) comprises the Program Objectives (is also known as Program Educational Objectives âˆ’ PEO) and Program Learning Outcomes (is also known as Program Outcomes âˆ’ PO). The program specifications were formulated after taking into consideration the view of stakeholders, and also the graduates attributes (issued by Universiti Teknologi Malaysia, BoEM, and Ministry of Higher Education). Petroleum graduates who have been working for four years or more in the industry must have all the competencies outlined in the PEO (achieved satisfactorily). Petroleum students must have all the competencies outlined in the PO upon graduation (achieved satisfactorily).